In-vitro ruminal ecosystem in buffaloes on concentrates and fat supplementation - Faiz Mohd Azmi, Amirul; Ahmad, Hafandi; Mohd Nor, Norhariani; Yong Meng, Goh; Zamri Saad, Mohd; Zuki Abu Bakar, Md; Abdul Rahman, Norafizah; Irawan, Agung; Jayanegara, Anuraga; Abu Hassim, Hasliza (ResearchersLinks, 2022)
The use of dietary supplementation such as concentrate and bypass fat to improve the buffalo performance warrants further investigations, especially in an in-vitro study. Even though several studies have reported the potential of supplementation in enhancing the growth of buffaloes, the effect on a different breeds of buffaloes, the potential to reduce methane production, and the changes in microbial populations remained unclear following different ratios of forage: supplementation feeding regime. This study described the effects of supplementing Brachiaria decumbens grass (G) received either concentrate (C) or mixed with bypass fat (B) supplement on the in-vitro rumen fermentation and microbial ecosystem of Murrah cross and Swamp buffaloes. Three males Murrah cross and Swamp buffaloes consuming 100% DM of fresh B. decumbens were used as rumen contents donors. The in-vitro ruminal fermentation and microbial population profiles were investigated. The study revealed that Diet C had the highest ether extract and gross energy, with optimum value of crude proteins but low in crude fiber compared to diets B and A. Total volatile fatty acids (TVFA) and their molars proportion, gas production, total fatty acids, total bacteria count, and total protozoa count increased in parallel with the concentrate levels in Diets B and C (P < 0.05) in both breeds. The result also revealed that Murrah cross and Swamp buffaloes showed comparable rumen fermentation patterns when treated with the same dietary treatments, but Swamp buffalo were significantly (P < 0.05) higher in Ruminococcus albus and total fatty acid. This study showed that supplementing concentrates solely or a mixture with bypass fat into a grass-based diet could decrease methane production, as well as methanogens without giving a detrimental effect on rumen fermentation but also increase the degree of fatty acids saturation partially via increasing the abundance of fibrolytic bacteria. Thus, both dietary treatments are highly recommended to enhance optimal rumen fermentation and eventually support production performance.